2023
DOI: 10.1186/s40001-023-01048-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance-based drug repurposing: searching for putative drugs with hypohidrosis or anhidrosis adverse events for use against hyperhidrosis

Abstract: Background Drug repurposing refers to the application of existing drugs to new therapeutic indications. As phenotypic indicators of human drug response, drug side effects may provide direct signals and unique opportunities for drug repurposing. Objectives We aimed to identify drugs frequently associated with hypohidrosis or anhidrosis adverse reactions (that is, the opposite condition of hyperhidrosis) from the pharmacovigilance database, which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The current study has identified potential drugs that can be repurposed against Pseudomonal, Staphylococcal, and Streptococcal infections through possible novel mechanisms. Very few studies have been conducted so far regarding the use of pharmacovigilance data for drug repurposing against various diseases such as hyperhidrosis (Liu et al, 2023), Raynaud's phenomenon (Zaza et al, 2020), Alzheimer's disease (Chrétien et al, 2021), and so forth. Liu et al (2023) have used the FAERS database whereas Zaza et al (2020) and B. Chrétien et al (2020) have used Vigibase (Chrétien et al, 2021; Liu et al, 2023; Zaza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study has identified potential drugs that can be repurposed against Pseudomonal, Staphylococcal, and Streptococcal infections through possible novel mechanisms. Very few studies have been conducted so far regarding the use of pharmacovigilance data for drug repurposing against various diseases such as hyperhidrosis (Liu et al, 2023), Raynaud's phenomenon (Zaza et al, 2020), Alzheimer's disease (Chrétien et al, 2021), and so forth. Liu et al (2023) have used the FAERS database whereas Zaza et al (2020) and B. Chrétien et al (2020) have used Vigibase (Chrétien et al, 2021; Liu et al, 2023; Zaza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been conducted so far regarding the use of pharmacovigilance data for drug repurposing against various diseases such as hyperhidrosis (Liu et al, 2023), Raynaud's phenomenon (Zaza et al, 2020), Alzheimer's disease (Chrétien et al, 2021), and so forth. Liu et al (2023) have used the FAERS database whereas Zaza et al (2020) and B. Chrétien et al (2020) have used Vigibase (Chrétien et al, 2021; Liu et al, 2023; Zaza et al, 2020). However, to the best of our knowledge, no study has been conducted so far that uses a pharmacovigilance‐based approach for the identification of repurposed drugs against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations